Implementation Of The New Student Admission System (SPMB) Policy At Sma Negeri 1 Mataram By The Department Of Education And Culture Of West Nusa Tenggara Province - Tatang Sudrajat; Rita Sulastini; Yuyun Yuniarsih; Farida Yuliaty; Kosasih; Aryani Kusuma Mukti (JURNAL ECONOMINA, 2026)
This research is motivated by the misalignment of admission pathways in the implementation of the New Student Admission System (SPMB) at SMA Negeri 1 Mataram, conducted by the Department of Education and Culture of West Nusa Tenggara Province. This policy is implemented as an effort to promote equitable access to and quality of education across all regions, particularly at the senior secondary education level. The main issues encountered in the implementation of this policy include a surge in applicants to favored schools, public resistance to the zoning system, and various technical and social obstacles. This research adopts a descriptive qualitative approach, utilizing observation, in-depth interviews, and documentation for data collection. Data analysis was conducted using the interactive model by Miles and Huberman, supported by Atlas.ti 25 software to map the findings. The study focuses on (1) the implementation of the SPMB policy, (2) supporting and inhibiting factors in the implementation process, and (3) strategies employed to overcome the challenges. The findings reveal that the SPMB policy at SMA Negeri 1 Mataram has been implemented in accordance with guidelines from the Education Department, yet still faces significant challenges such as domicile data manipulation, limited infrastructure, and insufficient public outreach. Key supporting factors include the school's commitment, readiness of the online system, and supportive regulations. Strategies undertaken include enhanced inter-institutional communication, adaptation of admission quota allocation, and improvements to digital services. This research recommends strengthening transparency, equal distribution of facilities across schools, and reinforcing monitoring and regular evaluation systems for the SPMB implementation. The findings are expected to serve as a reference for refining education policies, particularly in ensuring fair and equitable student admissions.